Effects of Intravenous Landiolol on Heart Rate and Outcomes in Patients with Atrial Tachyarrhythmias and Acute Decompensated Heart Failure: A Single-Center Experience - Yuko Matsui; Atsushi Suzuki; Tsuyoshi Shiga; Kotaro Arai; Nobuhisa Hagiwara (Adis, Springer Healthcare, 2019)
Abstract Objective Atrial tachyarrhythmias (ATAs) lead to clinical deterioration and worsening heart failure (HF) in patients with acute decompensated HF (ADHF). We evaluated the effects of the ultrashort-acting intravenous β1-blocker landiolol on the heart rate, hemodynamics, and outcome in patients with ATAs and ADHF. Methods A total of 67 consecutive hospitalized patients with ATAs and ADHF who were treated with landiolol (36 males, 67 ± 12 years) were included in this single-center retrospective study. The primary endpoints were changes in heart rate and systolic blood pressure from baseline during intravenous landiolol administration. The secondary endpoints included restoration of sinus rhythm and outcomes. Results The median maintenance dose of intravenous landiolol was 3.0 (range 1.0-12.0) μg/kg/min and the median treatment duration was 5 (range 1-24) days. Intravenous landiolol reduced heart rate (141 ± 17 beats/min at baseline to 99 ± 20 beats/min at 6 h, P < 0.001) without a marked reduction in blood pressure or deterioration of HF. During landiolol treatment, 15 (22%) patients had spontaneously restored sinus rhythm. Eight patients experienced in-hospital death, and 41 (69%) were discharged with sinus rhythm. During the follow-up of 16 ± 12 months, patients with sinus rhythm showed a lower frequency of rehospitalization due to worsening HF than patients with ATAs (5/41 vs. 7/18, P = 0.019). Conclusions Our results showed that intravenous landiolol reduces the heart rate without markedly decreasing blood pressure in patients with ATAs and ADHF. Approximately 70% of the discharged patients were in sinus rhythm, and these patients showed a lower frequency of rehospitalization due to worsening HF (UMIN-CTR no. UMIN000033650).